2014
DOI: 10.1080/19443994.2013.827776
|View full text |Cite
|
Sign up to set email alerts
|

Citric acid-modified acrylic micro and nanofibers for removal of heavy metal ions from aqueous media

Abstract: A B S T R A C TThe present work describes a new modification process for producing chelating fibers for removal of heavy metal ions from aqueous solutions. Commercial acrylic fibers were hydrolyzed with sodium hydroxide to convert the CN groups on the molecular chains of the polymer to carboxylic acid groups. To increase the density of carboxyl groups on the fibers surface, citric acid was grafted to carboxylic acid groups. Furthermore, for comparison of the effect of surface area on the adsorption capacity, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…33 In general, a higher surface area would result in a higher ion adsorption capacity. 34,35 Interestingly, MSPR could effectively remove 95.83% of Cd 2+ , although it had a lower BET surface area than that of SPR. It was reported that a decrease in surface area can improve heavy metal immobilization, 36 which may be one reason for the higher removal rate of MSPR than that of SPR.…”
Section: Effect Of the Modication Conditions On CD 2+ Removalmentioning
confidence: 99%
“…33 In general, a higher surface area would result in a higher ion adsorption capacity. 34,35 Interestingly, MSPR could effectively remove 95.83% of Cd 2+ , although it had a lower BET surface area than that of SPR. It was reported that a decrease in surface area can improve heavy metal immobilization, 36 which may be one reason for the higher removal rate of MSPR than that of SPR.…”
Section: Effect Of the Modication Conditions On CD 2+ Removalmentioning
confidence: 99%
“…Pure PTFE showed 0 L/m 2 /hr flux, whereas HPAMAM grafted PTFE membranes showed 635 ± 9 L/m 2 /hr flux. Approximately 1.42 g/m 2 Cu 2+ ions were adsorbed by the grafted polymer from an aqueous solution, with a desorption rate of 90% under index acidic conditions [45]. A few more reports on composite nanofiber mats are highlighted in Table 1.…”
Section: The Role Of Nanomaterials For Effective Pollutant Removalmentioning
confidence: 99%
“…Physical methods that include adsorption, ion exchange, fi ltration and membrane-fi ltration processes (nanofi ltration, reverse osmosis and electrodialysis) are widely used in industry because of their dye removal potentials and low operating costs [2]. Among these techniques, adsorption is known as equilibrium separation process, and generally, it does not result in the formation of harmful substances [9][10][11]. Adsorption has many advantages such as low initial cost, fl exibility and simplicity of design, ease of operation and insensitivity to toxic pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of polymers such as polyethylene oxide [13], chitosan [10,27], polyacrylonitrile [28], cellulose acetate [29] and polyvinyl alcohol (PVA) [28][29][30] have been used in the studies of wastewater treatments. Apart from these studies, in the present contribution, to the best of authors' knowledge, porosity comparison of the PVA nanofi bers and the effect of fi xation temperature and collection period on chemically crosslinked and water-stable PVA nanofi bers have been investigated for their reactive dye removal from wastewater for the fi rst time.…”
Section: Introductionmentioning
confidence: 99%